HE EFFECT OF GLINTS INDONESIA YOUTUBE CONTENT TO FULFILL THE INFORMATION NEEDS OF SUBSCRIBERS - Ramita Hapsari; Nurul Fadilah Sandy (Journal of Digital Media Communication, 2022)
The existence of social media Youtube as a medium for seeking various information provides an interesting fact of how influential Youtube is so that it can be accepted by the public as information with various contents. Glint Indonesia's Youtube content as a means to find career development content such as discussing content about the world of work and job hacks that are usually needed by job seekers to be successful at the interview stage or when they have to adapt to the world of work. The purpose of this study was to see the Effect of Glints Indonesia Youtube Content to Fulfill the Information Needs on Subscriber. This research uses quantitative research methods and the positivism paradigm. The data collection technique was carried out using a survey method using a questionnaire with a sample of 400 respondents referring to the slovin formula. The respondents in this study were subscriber Glint Indonesia’s Youtube channel. This study uses the Uses and Gratification Theory with the basic assumption that the audience is active and selective in sorting the media, so that it raises the motive for using the media and satisfaction with that motive. The results of this study stated that exposure to Glints Youtube content has a strong enough to Fulfill the Information Needs of Glints Youtube channel on subscribers with a percentage of 40.7% so it can be concluded that there is an effect of exposure to Glints Youtube content on the fulfillment of information needs of subscribers.